KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA SEKOLAH DASAR NEGERI 17 BANDA ACEH. - Murniati AR, Bahrun, Cut Aja Irawati. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: A principal as a leader in educational institution has a strategic role in improving the professional competence of teachers. The purpose of this study was to find out the formulation of programs, implementation of strategies, and obstacles faced by the principal in improving professional competence of teachers. This study used descriptive method with qualitative approach. The techniques of data collection were observation, interview, and documentation. The subjects of this study were principal, teachers, supervisor, and Head of Division of Primary Education of Banda Aceh City. The results of this study showed that: (1) the programs from the principal in improving professional competence of teachers were started by holding deliberation among principal, vice principal, senior teachers, and school committee. The designed programs, long-term and short-term programs were referred to implementation instructions and technical instructions from Department of Education, Youth, and Sport of Banda Aceh City. All guidelines and programs were documented as foundation for the principal in implementing activities which aimed to the improvement of professional competence of teachers. (2) The principal applied appropriate strategies and suitable for teachers’ condition in the effort to improve professional competence. The strategies or approaches used to improve the professional competence of teachers were persusasive approaches. The democratic leadership style was combined with authoritarian leadership style when there were problems as stated in standard rules. (3) The obstacles faced by the principal in improving professional competence of teachers were the lack of funds for teacher training outside office hours, small number of teachers did not active, the training outcome did not affect their colleagues, and there were small number of teachers qualifications. Keywords: Leadership, Principal, and Professionalism of Teacher.Abstrak: Kepala sekolah sebagai pemimpin lembaga pendidikan memiliki peran yang strategis dalam meningkatkan kompetensi profesional guru. Tujuan penelitian ini untuk mengetahui: perumusan program, strategi pelaksanaan, dan hambatan yang ditemui kepala sekolah dalam meningkatkan kompetensi profesional guru. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data: observasi,  wawancara, dan studi dokumentasi. Subjek penelitian   kepala  sekolah dan  guru, pengawas, serta Kabid Dikdas Kota Banda Aceh.   Hasil  penelitian   menunjukkan   bahwa:   1) Program kepala sekolah dalam meningkatkan kompetensi profesional guru mekanisme perumusannya diawali dengan pelaksanaan musyawarah antara kepala sekolah, wakil kepala sekolah, guru senior dan komite sekolah. Program-program yang disusun, program jangka panjang, menengah dan jangka pendek semuanya berpedoman pada petunjuk pelaksana (juklak) dan petunjuk teknis (juknis) dari Dinas Pendidikan Pemuda dan Olahraga Kota Banda Aceh. Semua pedoman dan program ini sudah terdokumentasi sebagai dasar bagi kepala sekolah dalam melaksanakan kegiatan yang bersasaran langsung untuk peningkatan kompetensi profesional guru; 2)  Kepala sekolah menerapkan strategi yang cocok dan sesuai dengan kondisi guru dalam upaya meningkatkan kompetensi profesional. Strategi  yang digunakan untuk meningkatkan kompetensi profesional guru adalah dengan mengutamakan pendekatan persuasif. Gaya kepemimpinan yang digunakan sangat demokratis tetapi kalau masalahnya sudah ada aturan baku kepala sekolah sering bersikap sebagai pemimpin yang otoriter; dan 3) Hambatan yang ditemui kepala sekolah dalam meningkatkan kompetensi profesional guru antara lain terbatasnya program untuk pelatihan guru di luar jam dinas, masih ada sebagian kecil guru tidak aktif dan hasil penataran belum mampu mengimbas kepada  temannya. Sebagian  kecil  guru  masih  ada yang belum berpendidikan sarjana.Kata kunci:  Kepemimpinan, Kepala Sekolah, dan Kompetensi Profesional Guru.